Begonia rigidifolia ssp. sonhungii (sect. Petermannia, Begoniaceae), a new subspecies from limestone hills in Central Vietnam - Lin, Che-Wei; Phan, Luong Cong Son; Nguyen, Ngoc Hung (Phytotaxa, 2021)
Begonia rigidifolia Aver. ssp. sonhungii C.W.Lin (sect. Petermannia, Begoniaceae) from Central Vietnam is hereby described and illustrated as new. It resembles B. rigidifolia ssp. rigidifolia, but differs in its very sparsely puberulous (vs. glabrous), darker toned lamina that is embellished with a pale green broad band (vs. emerald green lamina with irregular radiantly arranged dark spots), stamens widely obovate (vs. obovate) and capsule with wider abaxial wing 6–10 mm (vs. 2–3 mm).